Revision of Zapatodes Orlandin, Piovesan & Carneiro, 2025 (Lepidoptera: Bombycoidea, Apatelodidae) with description of seven new species - Orlandin, Elton; Simões, Talitta; Piovesan, Mônica; Carneiro, Eduardo (Zootaxa, 2026)
Zapatodes is a Neotropical genus of apatelodid moths (Lepidoptera, Bombycoidea) that was proposed to encompass seven species previously placed in Apatelodes Packard, 1864 and Olceclostera Butler, 1879. The dissection of specimens with similar habitus revealed consistent morphological differences in the genitalia, suggesting the presence of several undescribed species and prompting a taxonomic revision of the genus. In this study, we describe seven new species in this genus: Zapatodes amada Orlandin & Piovesan sp. nov., Zapatodes chorotega Orlandin & Simões sp. nov., Zapatodes kambeba Orlandin, Piovesan & Carneiro sp. nov., Zapatodes miranha Orlandin, Piovesan & Carneiro sp. nov., Zapatodes mundurukania Orlandin, Piovesan & Carneiro sp. nov., Zapatodes pimenteira Orlandin & Piovesan sp. nov., and Zapatodes sullivani Orlandin & Simões sp. nov. Additionally, to ensure unambiguous identification of names, a neotype was designated for Zapatodes ennomoides (Walker, 1865). This revision doubles the number of known species in the genus to 14, significantly expanding our knowledge of the diversity, distribution, and biology of Apatelodidae.